Optimizing Patient-Centered Care: A Review of Interdisciplinary Approaches in Nursing, Laboratory, and Pharmacy Services within Saudi Arabian Healthcare Systems - Amer Maseer Aldhafeeri; Reem Thaqeel Nadi Aldhafeeri; Fahdah Murawwih Oshaywi Aldhafeeri; Ali Khalaf Almuways; Majed Ahmed Alshammari; Musa Ghafil Al Dhafiri; Khalid Suwailem Alanazi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This qualitative study aimed to explore interdisciplinary approaches to optimizing patient-centered care within nursing, laboratory, and pharmacy services in Saudi Arabian healthcare systems. Methods: Semi-structured interviews were conducted with a purposive sample of 24 healthcare professionals (8 nurses, 8 laboratory staff, 8 pharmacists) working in Hafr El Batin. Interview transcripts underwent thematic analysis. Results: Three main themes emerged: 1) Communication and collaboration, with subthemes of interdisciplinary meetings, shared decision-making, and mutual respect; 2) Patient engagement, with subthemes of education, empowerment, and cultural competence; and 3) Systemic factors, with subthemes of supportive leadership, resources and staffing, and continuous improvement. Conclusions: Optimizing patient-centered care requires an interdisciplinary approach built on effective communication, patient engagement, and a supportive system. Implementing the identified strategies, while addressing challenges, can enhance patient-centeredness across nursing, laboratory, and pharmacy services in Saudi Arabia and beyond.